(Don't) Keep Your Nose Out of my Business: an Experimental Study on the Efficacy of Scent Marketing in Retail Envronment - Tierandha, Aliekha; Iskandar, Budi Permadi (Journal of Business and Management, 2014)
Our senses are frequently bombarded by a wide array of distinguished atmospheric cues anytime we go into a marketplace. Now, marketers venture to signaling invitation through a relatively unexplored sense, the sense of smell. Does the idea make scents? This study aims to investigate whether using ambient scent in a retail setting is actually prolific by observing its effect on the number of shoppers visiting the store. A single-case experiment on a local female fashion store was conducted. The findings suggest that ambient scent does not influence the number of the store’s shoppers.Keywords: ambient scent, scent marketing, sense of smell, shopper behaviour, retail